Application of computerized cognitive test battery in major depressive disorder: a narrative literature review. (2nd May 2022) - Cao, Bing; Xiao, Mingyue; Chen, Ximei; Zhao, Yuxiao; Pan, Zihang; McIntyre, Roger S.; Chen, Hong
Abstract: Background: Major depressive disorder (MDD) is a chronic and debilitating relapsing-remitting mood disorder, characterized by psychological, cognitive, and behavioral disturbances. The assessment of cognitive dysfunction in individuals with MDD has increasingly become a topic of concern in recent years. Aims: To pool and compare the characteristics of various cognition evaluation tools. Method: Overview of recent research in application of computerized cognitive test battery in MDD. Results: With recent technological advances in mobile health technologies and the ubiquity of smartphones, the use of traditional tools is no longer sufficient to monitor the dynamic changes of an individual's cognitive performance, which may be influenced by many factors, including, but not limited to, disease course and medications. Computerized tests have many advantages over traditional neuropsychological testing, chiefly in terms of time and cost savings, accurate recording of multiple response components, and the ability to automatically store and compare performance between testing sessions. In the following review, we summarized cognitive impairment characteristics of MDD, introduced traditional assessment tools of cognitive function in MDD, and reviewed the development of the current computerized cognitive test batteries for MDD. The comparisons among cognitive function evaluation tools were also performed. Conclusions: It is our belief that the improvement of existing novel computerized cognitive test batteries, the development of more comprehensive and easy-to-operate scales, verification techniques and multiple follow-up surveys among large sample populations may provide valuable clues for the evaluation and tracking of cognitive function in individuals with MDD.